Comparação entre metodologias para estimativa de vazão em canal de irrigação no arroio chasqueiro/rs - Ludwig, Rafael [UNESP]; Silva, Diego De Mello; Damé, Rita De Cássia Fraga; Teixeira, Claudia Fernanda Almeida (My University, 2014)
The federal law 9433/97 of water resources is based on the premise that water is a finite asset and endowed with economic value. Among the human activities, irrigated agriculture is the one that requires a greater consume of water, and because of this fact, the district of irrigation of the Chasqueiro stream is seeking better control on derivation of water rates to irrigated rice fields. Thus, the objective of this study was to evaluate the flow rate distributed in areas along the C2 canal by comparing 2 methods of flow rate determination. Moreover, the study aimed to analyze the variation between the methods and identify the need for adjustment of the coefficient of discharge adopted in the method of the orifices. It is thought that the study will contribute to promote an efficient management of irrigation. To this end, a survey was conducted to determine the areas served by the canal and the flow rates in different points of it. These parameters were determined based on the speed of water runoff (pygmy meter method), the analysis of upstream and downstream levels and also on the opening of the floodgates at the same points (orifice method). Afterward, data were compared in order to determine percentage differences. According to the results, variations of 8.82% and 306.25% in flow rate values were found between the 2 methods. It was also observed that, although the mean flow rate was according to that provided by the cooperative, it was not uniform through canal 2, revealing that the problem concerning water supply was not based on the release of enough levels to meet the irrigated areas, but on inadequate adjustments of the floodgates. This finding shows the need of further studies on the calibration of structures of control which would lead to more accurate measurement of flow rates by the method of the orifices.
Comparison between methods for estimating the flow rate in the irrigation canal of the chasqueiro/rs stream
Keywords: Discharge curve; Flood irrigation; Water flow measurement